Stability and neurotoxic impact of organophosphate pesticides in aqueous environments - Anićijević, Vladan J.; Tasić, Tamara; Milanković, Vedran; Karkalić, Radovan M.; Lazarević Pašti, Tamara D. (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: Organophosphates are widely used nowadays. They have applications as pesticides, drugs, plasticizers, flame retardants, or chemical warfare agents. Their acute toxicity is ascribed to inhibiting acetylcholinesterase (AChE), a key enzyme in the transmission of nerve impulses in animals. Their toxic effects manifest by acetylcholine accumulation in the nerve synapses and can lead to paralysis or death. Organo-thiophosphate pesticides (OPs) are used in large quantities. Their oxo-analogs can also be found in the environment due to oxidation. Once accumulated in the environment, they exhibit toxic effects on non-target organisms.Methods: The hydrolysis of OPs in different pH was systematically analyzed, and their neurotoxic effects were evaluated. The concentration of the investigated pesticides during decomposition was monitored by ultra-performance liquid chromatography (UPLC). At the same time, a decrease in the toxicity of the treated samples was observed by measuring the activity of the enzyme AChE.Results: OPs decompose rapidly in alkaline aqueous solutions but are highly stable in acidic solutions. Chlorpyrifos hydrolyzes the fastest and dimethoate the slowest. The toxicity of these OP solutions decreases over time, indicating that more toxic products were not formed. Conclusion: The presented results can provide a sound basis for further efforts to find simple and efficient decomposition methods of OPs.
Keywords: organophosphate; pesticide; pH stability; toxicity